A Preliminary Observation of Increased Glial Cell Line-Derived Neurotrophic Factor in Manic Switch due to Electroconvulsive Treatment in Depressive Patients. Issue 3 (September 2015) - Tunca, Zeliha; Bayın, Mehmet; Alkın, Tunç; Özerdem, Ayşegül; Resmi, Halil; Akan, Pınar
<x xml:space="preserve">Abstract</x> Objective Neurotrophic factors are known to be involved in the pathogenesis of mood disorders. However, the precise neurobiology underlying relapse into depression or switch to mania under antidepressant treatment is not fully understood. Evidence suggests the role of neuroplasticity in these processes. Method Brain-derived neurotrophic factor and glial cell line-derived neurotrophic factor (GDNF) serum levels were measured concomitantly during electroconvulsive treatment (ECT) in 30 depressive patients (25 patients with unipolar, 5 with bipolar depression), including those who relapsed into depression (n = 6) or switched to mania (n = 3) within 1 to 4 weeks after the end of the ECT, and in 33 healthy volunteers. Results Despite significant decrease in depression scores, the levels of brain-derived neurotrophic factor did not significantly change during the ECT, also in the patients who relapsed into depression or switched to mania. However, GDNF levels were lower in the ECT responders compared with pre-ECT levels (z = −2.203; P = 0.01) and increased in manic switch compared with the ECT responders (z = −2.761; P = 0.001) (Cohen d = −1.75; effect size r = −0.66) and healthy controls as well (P = 0.044). Conclusions Our data suggest the role of GDNF in manic switch and the involvement of glial system in the pathogenesis of mood disorders.